2021
DOI: 10.3389/fnins.2021.701308
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Tissue Inflammation and Blood-Brain Barrier Disruption to Brain Softening in a Mouse Model of Multiple Sclerosis

Abstract: Neuroinflammatory processes occurring during multiple sclerosis cause disseminated softening of brain tissue, as quantified by in vivo magnetic resonance elastography (MRE). However, inflammation-mediated tissue alterations underlying the mechanical integrity of the brain remain unclear. We previously showed that blood-brain barrier (BBB) disruption visualized by MRI using gadolinium-based contrast agent (GBCA) does not correlate with tissue softening in active experimental autoimmune encephalomyelitis (EAE). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 56 publications
(150 reference statements)
3
18
1
Order By: Relevance
“…Under neuroinflammatory conditions, we observed a mild effect in females and a significant softening of the midbrain of 5% in male EAE, although previous studies reported a global softening in female EAE brains [17][18][19] as well as for MS patients of both sexes [12]. This discrepancy could be explained by the limitation of the analyzed region, which was restricted to a single coronal slice, and did not cover the usually affected cerebellum or optic nerve [63,64].…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…Under neuroinflammatory conditions, we observed a mild effect in females and a significant softening of the midbrain of 5% in male EAE, although previous studies reported a global softening in female EAE brains [17][18][19] as well as for MS patients of both sexes [12]. This discrepancy could be explained by the limitation of the analyzed region, which was restricted to a single coronal slice, and did not cover the usually affected cerebellum or optic nerve [63,64].…”
Section: Discussioncontrasting
confidence: 65%
“…To comply with animal welfare guidelines, all mice with a score higher than 3 were euthanized and removed from the study ( n female = 2, n male = 1). The EAE model using SJL mice has been shown to be more suitable for cerebral MRE studies than EAE in C57BL/6, since PLP-induced EAE in SJL consistently leads to the development of brain lesions and to elasticity alterations in brain structures [ 17 , 18 , 19 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations